Spatiotemporal extracellular matrix modeling for in situ cell niche studies. (31st August 2021) - Olesen, Kim; Rodin, Sergey; Mak, Wing Cheung; Felldin, Ulrika; Österholm, Cecilia; Tilevik, Andreas; Grinnemo, Karl‐Henrik
Abstract: Extracellular matrix (ECM) components govern a range of cell functions, such as migration, proliferation, maintenance of stemness, and differentiation. Cell niches that harbor stem‐/progenitor cells, with matching ECM, have been shown in a range of organs, although their presence in the heart is still under debate. Determining niches depends on a range of in vitro and in vivo models and techniques, where animal models are powerful tools for studying cell‐ECM dynamics; however, they are costly and time‐consuming to use. In vitro models based on recombinant ECM proteins lack the complexity of the in vivo ECM. To address these issues, we present the spatiotemporal extracellular matrix model for studies of cell‐ECM dynamics, such as cell niches. This model combines gentle decellularization and sectioning of cardiac tissue, allowing retention of a complex ECM, with recellularization and subsequent image processing using image stitching, segmentation, automatic binning, and generation of cluster maps. We have thereby developed an in situ representation of the cardiac ECM that is useful for assessment of repopulation dynamics and to study the effect of local ECM composition on phenotype preservation of reseeded mesenchymal progenitor cells. This model provides a platform for studies of organ‐specific cell‐ECM dynamics and identification of potential cell niches. Abstract : Spatiotemporal extracellular matrix modeling facilitates the identification of cell‐niches by combining decellularized whole organ sections and recellularization with a new algorithm for automatic generation of density maps and cluster‐analysis for identification of regions of interest.